2014
DOI: 10.1016/j.bbi.2013.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Training status and sex influence on senescent T-lymphocyte redistribution in response to acute maximal exercise

Abstract: This study highlights important sex and training status differences in the senescent and naïve T-lymphocyte redistribution in response to exercise that warrants further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 177 publications
3
51
0
Order By: Relevance
“…27 Another recent study showed that 1 week of intensified training in trained male cyclists impaired the egress of naive CD8 + T lymphocytes (CD27 + CD45RA + ) and cytotoxic T lymphocytes from the blood after exercise. Preliminary work indicates that sex may moderate the effects of exercise on T-cell redistribution, 29 and indeed other measures of immunity (reviewed elsewhere), 30 but future work is required to elucidate a role for sex hormones. Preliminary work indicates that sex may moderate the effects of exercise on T-cell redistribution, 29 and indeed other measures of immunity (reviewed elsewhere), 30 but future work is required to elucidate a role for sex hormones.…”
Section: Exercise and Acquired Immunitymentioning
confidence: 99%
“…27 Another recent study showed that 1 week of intensified training in trained male cyclists impaired the egress of naive CD8 + T lymphocytes (CD27 + CD45RA + ) and cytotoxic T lymphocytes from the blood after exercise. Preliminary work indicates that sex may moderate the effects of exercise on T-cell redistribution, 29 and indeed other measures of immunity (reviewed elsewhere), 30 but future work is required to elucidate a role for sex hormones. Preliminary work indicates that sex may moderate the effects of exercise on T-cell redistribution, 29 and indeed other measures of immunity (reviewed elsewhere), 30 but future work is required to elucidate a role for sex hormones.…”
Section: Exercise and Acquired Immunitymentioning
confidence: 99%
“…There are distinct sex differences in the T-cell changes with acute exercise (Brown et al 2014). Our study did not include women; therefore, further research is warranted to investigate whether there are any sex differences in T ANG cell changes with acute bouts of exercise.…”
Section: Limitationsmentioning
confidence: 99%
“…The effects of cardiorespiratory fitness appeared to be largely independent of age, body composition, and CMV serostatus [69]. Similar observations have been made in young adults who engage in structured exercise that is typical of training for competitive team sports [70, 71]. In the elderly, however, an active lifestyle only appears to limit the accumulation of late-stage differentiated T cells and does not appear to substantially affect the proportions of naïve T cells [72].…”
Section: The Effects Of Aerobic Exercise Training On Late-stage DImentioning
confidence: 76%